Mirah Bogor Hotel: Mastering Public Relations to Build a Lasting Brand Image - Putranto, Diyan; Halawa, Fransiscus Amonio; Widodo, Rintis Eko; Due, Laurensius Reinald Diansilves; Siagian, Kartini (East Asian Journal of Multidisciplinary Research, 2024)
This article investigates the role of public relations in building the image of Mirah Bogor Hotel. Using a qualitative descriptive research method, the study found that effective public relations strategies include promotion, events, collaboration with media, and the use of social media. The research also highlighted that Corporate Social Responsibility (CSR) is a crucial strategy in building a positive hotel image. The challenges faced by hotels in building a positive image include communication crises, societal changes, and industry competition. The study's conclusion emphasizes the significant role of public relations in building and maintaining a positive hotel image. Recommendations for public relations practitioners include improving service quality and facilities, and being prepared to handle crises. This article comprehensively discusses the role of public relations in building hotel images, as well as the strategies and challenges faced by Mirah Bogor Hotel.